An Exploration of Osing Youth Mental Health in Suicide Mitigation Efforts - Leni Anggraini; Novita Surya Putri; Ricka Ayu Yuliyasari; Ani Firda; Sholihin Sholihin (GLOBAL HEALTH SCIENCE GROUP, 2026)
Mental stability refers to a condition of psychological stability that allows people to handle life's challenges, reach their full potential, acquire knowledge effectively, work productively, and make positive contributions to their communities. The Osing tribe has a unique tradition of integrating biological, psychological, social, and spiritual aspects holistically, which is believed to play a role in maintaining health. This research seeks to investigate the mental health of Osing tribe adolescents in achieving mental wellbeing as a suicide prevention strategy. The study explores the efforts and strategies of Osing tribe adolescents in achieving mental wellbeing. The framework of this research employs a qualitative methodology utilizing a phenomenological perspective. The individuals involved in this research were six Osing tribe adolescents from Kemiren Village. This research employed a semi-structured interview guide as the research instrument. The collected data were transcribed and then validated by the participants. The sampling technique used in this study was purposive sampling. There were six participants in this study, all of whom were Osing teenagers aged between 10 and 21 years old. The Colaizzi method was employed to analyze the data transcripts. The analysis of data coding was performed with the help of Nvivo 12 software. Three themes and eight subthemes were identified. The identified themes are Stress, Osing Youth Activities, and Social Support. Osing ethnic group youth demonstrated that they are like other youth in general, who also experience stress. Osing ethnic group adolescents demonstrated stress resolution processes through coping mechanisms applied with various strategies, including physical strategies (traditional dancing, playing gamelan musical), cognitive strategies by managing time, emotional strategies by sharing concerns, apologizing, and reminding each other, and behavioral strategies by resting when there are no activities. Osing tribe teenagers also receive good emotional and social support. Osing tribe adolescents possess adaptive coping resources for stress through their daily routine of artistic activities. Osing tribe adolescents have four domains that contribute to mental well-being: family, community, school, and village government.